2010
DOI: 10.1530/rep-09-0504
|View full text |Cite
|
Sign up to set email alerts
|

Luteal blood flow and concentrations of circulating progesterone and other hormones associated with a simulated pulse of 13,14-dihydro-15-keto-prostaglandin F2α in heifers

Abstract: Progesterone and luteal blood flow effects of an i.u. 2-h infusion of 0.25 mg/h of prostaglandin F 2a (PGF) that simulated a natural pulse of 13,14-dihydro-15-keto-PGF (PGFM) were compared to the effects of a single bolus i.u. injection of PGF (4 mg) that induced complete luteolysis in heifers. Blood sampling and an estimate of the percentage of luteal area with colour-Doppler signals of blood flow were performed every 2 min for 20 min and less frequently thereafter for 6 h. After the beginning of PGF infusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
1
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 44 publications
6
38
1
3
Order By: Relevance
“…Both P4 and CL blood flow appear to respond to this luteolytic dose of PGF [10,36]. Furthermore, in this study the overall trends in CL blood flow area and ratio appear to be in agreement with the expression of pro and antiangiogenic factors described throughout the lifecycle of the CL [37].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Both P4 and CL blood flow appear to respond to this luteolytic dose of PGF [10,36]. Furthermore, in this study the overall trends in CL blood flow area and ratio appear to be in agreement with the expression of pro and antiangiogenic factors described throughout the lifecycle of the CL [37].…”
Section: Discussionsupporting
confidence: 83%
“…Color Doppler ultrasound of the CL is a relatively new method for analyzing CL physiology [1]. Using color flow as opposed to spectral Doppler, luteal blood flow has been studied extensively during spontaneous and induced luteolysis [8][9][10] and throughout the estrous cycle [11]. Relatively few studies have reported the vascular changes in the CL between pregnant and nonpregnant animals [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…However, the 1.0-or 0.25-mg doses require sequential treatments (e.g., every 12 h) for complete luteolysis in a stepwise fashion, demonstrating the importance of natural PGF pulsatility. The nonphysiological increase did not occur when a PGFM pulse was simulated by intrauterine infusion of PGF in heifers [14,25] or by an intravenous infusion in mares [26]. Furthermore, an initial increase in progesterone was not detected in blood samples collected every 15 min from heifers in temporal association with the beginning nadir or ascending portion of a spontaneous PGFM pulse [28].…”
Section: Nonphysiological Progesterone Increase In Cattle and Horsesmentioning
confidence: 92%
“…Recent studies have shown that the immediate progesterone response to PGF treatment is nonphysiological in both cattle [14,25] and horses [26,27]. In both species, the nonphysiological increase occurs when a PGF dose is much higher than the animal experiences with a natural PGF pulse.…”
Section: Nonphysiological Progesterone Increase In Cattle and Horsesmentioning
confidence: 99%
See 1 more Smart Citation